URGENSI QAWA’IDH FIQHIYYAH DALAM PENGEMBANGAN HUKUM ISLAM - Kholidah Kholidah (IAIN Padangsidimpuan, 2023)
This study aims to analyze the urgency of qawa'id fiqhiyyah in the development of Islamic law. The rationale departs from the definition of the fiqhiyyah rule itself, namely a collection of syara' laws from various legal events that have the same 'illat. This meaning assumes that fiqhiyyah rules actually have a role in the development of Islamic law. Bearing in mind that each rule contains 'illat law, legal rationale and also philosophical values that can be used as a basis for establishing a law in a new case. This study uses a normative juridical method, with secondary data in the form of three legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. The data were taken from the literature as a data source, then analyzed and described systematically. The conclusions drawn are, 1) qawa'idh fiqhiyyah can be used as an alternative in resolving legal issues for which there is no explanation. 2) Qawa'id fiqhiyyah contains quite high dynamic values. 3), Qawa'id fiqhiyyah is able to realize legal elasticity to be applied in various contexts and. 4) Qawa'id fiqhiyyah contains the values of the contextualization of Islamic law.